Experiential Learning in Engineering Education: A Book Review (Asean Journal of Engineering Education, 2023)
"Experiential Learning in Engineering Education" by Alan L. Steele offers an in-depth exploration of experiential learning (EL) within engineering education, uniquely enriched by global research, case studies, and the author’s extensive experience and theoretical grounding. Steele’s work stands out for its comprehensive coverage of EL applications, addressing the evolving landscape of post-pandemic education and emphasizing the expansive nature of EL. The book is invaluable for faculties, educators, and researchers, providing practical strategies, insights, and a solid theoretical foundation. Its eleven chapters are grounded in educational theories like Kolb's Cycle and reflective practice, and are enriched by Steele's extensive experience in education and practical application. The book particularly stands out for its incorporation of evident-based EL strategies, including innovative laboratory methods, flipped classrooms and best practices from cross-disciplines. However, it could benefit from a more balanced chapter depth, a broader narrative perspective, clearer guidance on student reflection, and addressing the implications of AI tools in assessments. Future editions should aim for a more equitable exploration across chapters, inclusion of diverse stakeholder perspectives, and enhanced visual content. By addressing these areas, the book has the potential to solidify its position as a pivotal resource in engineering education, shaping future generations of engineering educators.
Keywords: Experiential Learning; Book Review; Engineering Education; Reflection; education post-COVID